EFEKTIVITAS KEBIJAKAN PEMBAYARAN UANG PENGGANTI DALAM TINDAK PIDANA KORUPSI DI INDONESIA - Ananta Prathama; Widya Puspa Prameswari; Silvia Wahyu Pradana (Jurnal Penelitian Administrasi Publik, 2020)
Various attempts were made by the government to eradicate corruption. One of them makes additional criminal policies in the form of replacement money. The effort apparently has not produced specific results because the rate of corruption continues to increase every year. The purpose of this research is to find out how far the effectiveness of the policy of implementing replacement payments in corruption and to find out the obstacles faced in paying compensation money in corruption and how to overcome them. This study uses a normative legal research method with a qualitative approach. The results of this study indicate that the replacement money policy has not been effective. Keywords: Effectiveness of policies, Substitute money, Corruption